IMPLEMENTATION OF ORDER MANAGEMENT SYSTEM CAFFE-BASED MENU FOOD STACK AND QUEUE - Sari, Dita Novita; Susilowati, Tri; Asiyani, Lucy; Alfarizi, Dimas (Asia Information System Journal, 2025)
This study explores the implementation of a food ordering management system in cafes using stack and queue data structures. The system is designed to tackle challenges related to the recording, queue sorting, and tracking of order history with improved efficiency and accuracy. A queue is utilized to manage incoming orders based on the First In First Out (FIFO) principle, while a stack is employed to store order history following the Last In First Out (LIFO) principle. The system is developed with a Tkinter-based user interface and tested using various software testing methods, including unit testing, integration testing, system testing, and acceptance testing. The results from these tests show that the system functions as expected, offering high accuracy and streamlining cafe staff operations. By improving operational efficiency, the system also enhances customer satisfaction. This research contributes to the ongoing development of digital solutions in the culinary industry and offers potential for broader applications in other sectors that require efficient queue management and service history tracking.